Distinct hormonal and morphological control of dormancy and germination in Chenopodium album dimorphic seeds - Loades, Eddison; Pérez, Marta; Turečková, Veronika; Tarkowská, Danuše; Strnad, Miroslav; Seville, Anne; Nakabayashi, Kazumi; Leubner-Metzger, Gerhard (Frontiers in Plant Science, 2023)
Dormancy and heteromorphism are innate seed properties that control germination timing through adaptation to the prevailing environment. The degree of variation in dormancy depth within a seed population differs considerably depending on the genotype and maternal environment. Dormancy is therefore a key trait of annual weeds to time seedling emergence across seasons. Seed heteromorphism, the production of distinct seed morphs (in color, mass or other morphological characteristics) on the same individual plant, is considered to be a bet-hedging strategy in unpredictable environments. Heteromorphic species evolved independently in several plant families and the distinct seed morphs provide an additional degree of variation. Here we conducted a comparative morphological and molecular analysis of the dimorphic seeds (black and brown) of the Amaranthaceae weed Chenopodium album. Freshly harvested black and brown seeds differed in their dormancy and germination responses to ambient temperature. The black seed morph of seedlot #1 was dormant and 2/3rd of the seed population had non-deep physiological dormancy which was released by after-ripening (AR) or gibberellin (GA) treatment. The deeper dormancy of the remaining 1/3rd non-germinating seeds required in addition ethylene and nitrate for its release. The black seeds of seedlot #2 and the brown seed morphs of both seedlots were non-dormant with 2/3rd of the seeds germinating in the fresh mature state. The dimorphic seeds and seedlots differed in testa (outer seed coat) thickness in that thick testas of black seeds of seedlot #1 conferred imposed-coat dormancy. The dimorphic seeds and seedlots differed in their abscisic acid (ABA) and GA contents in the dry state and during imbibition in that GA biosynthesis was highest in brown seeds and ABA degradation was faster in seedlot #2. Chenopodium genes for GA and ABA metabolism were identified and their distinct transcript expression patterns were quantified in dry and imbibed C. album seeds. Phylogenetic analyses of the Amaranthaceae sequences revealed a high proportion of expanded gene families within the Chenopodium genus. The identified hormonal, molecular and morphological mechanisms and dormancy variation of the dimorphic seeds of C. album and other Amaranthaceae are compared and discussed as adaptations to variable and stressful environments.